Parental migration and left-behind children in Georgia - school teachers' experience and perception: a qualitative study - Antia, Khatia; Berner-Rodoreda, Astrid; Winkler, Volker (BMC public health, 2022)
Introduction Georgia, like other Eastern European countries, showed a dramatic increase of international labour emigration after becoming independent in 1991. The collapse of the Soviet Union caused economic instability, unemployment and poverty resulting in labour migration. Since then, thousands of children have been left behind in the care of extended family members while their parents work abroad. The aim of this study is to explore schoolteachers' perceptions on parental migration and left-behind children (LBC) in Georgia as schoolteachers are the main contact persons for LBC and their caregivers. Methods We conducted six focus-group discussions with public school teachers, namely class-tutors and six in-depth interviews with school principals from two migrant sending regions. We applied reflexive thematic analysis to systematically analyse the data and identify main and sub-themes. The contextual model of family stress underpins this study. Results We identified the following themes expressed by both, teachers, and school principals: social and economic impact of migrant labour and relationships between schools and migrant families. School teachers and principals acknowledged some positive aspects of migrant labour, but primarily perceived parental migration as a negative experience for children leading to problems in mental health, well-being, and academic performance. Structural factors, lack of support and lack of community involvement were expressed to further worsen the situation. Teachers saw themselves as one of the main supporters for LBC while they described the role of caregivers ranging from caring to unhelpful or even destructive. School principals stated mitigating the situation by regular meetings with class tutors, extra-tutoring for LBC, psychological counselling, and developing/enacting internal guidelines. Conclusions Our findings suggest that LBCs and transnational families could benefit from the provision of psychological services at schools.
Gesehen am 21.12.2022